Enteritis of the ileal conduit as an adverse event related to immune checkpoint inhibitor use - Ko Kobayashi; Kohei Hashimoto; Toshiaki Tanaka; Naoya Masumori (IJU Case Reports)
Introduction Gastroenterocolitis is one of the adverse events related to immune checkpoint inhibitors. However, inflammation of the intestinal lesion used for urinary diversion is not well known as an adverse event related to their use. Case presentation A patient with metastatic bladder cancer was administered pembrolizumab as second‐line treatment. After 12 days of administration, he felt abdominal distention. Computed tomography demonstrated thickening of the ileal conduit wall and bilateral hydronephrosis. Biopsy of the ileal conduit revealed inflammatory granulation tissue. Biopsy of the sigmoid colon also revealed colitis. Therefore, we diagnosed enterocolitis including the ileal conduit related to pembrolizumab. We then started to administer 30 mg prednisolone. After this treatment, we confirmed improvement of the clinical symptoms and healing of the ileal conduit mucosa. Conclusion Inflammation of an ileal conduit can occur as an immune‐related adverse event caused by metastatic urothelial carcinoma treatment with pembrolizumab.